The population based cognitive testing in subjects with SARS-CoV-2 (POPCOV2) study: longitudinal investigation of remote cognitive and fatigue screening in PCR-positive cases and negative controls - von Etzdorf, Alina; Harzen, Maja; Heinrichs, Hannah; Seifert, Henning; Groiß, Stefan J.; Balloff, Carolin; Feldt, Torsten; Jensen, Björn-Erik Ole; Lüdde, Tom; Bernhard, Michael; Schnitzler, Alfons; Goebels, Klaus; et al. (Frontiers in Human Neuroscience, 2024)
BackgroundThe majority of people infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) only show mild respiratory symptoms. However, some patients with SARS-CoV-2 display neurological symptoms. Data on the exact prevalence and course of cognitive symptoms are often limited to patient reported outcomes or studies recruited at specialized centers.MethodsFor this prospective, non-interventional population based POPCOV2 study, 156 subjects who performed SARS-CoV-2 testing in the Düsseldorf metropolitan area at public test centers between December 2020 and February 2022 were recruited by handouts. SARS-CoV-2-positive and negatively tested subjects were included within the first seven days after the PCR test results. Cognitive testing was performed at baseline during home quarantine and after 4–6 as well as 12–14 weeks of follow-up. Individuals were examined remotely by videocalls using the Symbol Digit Modalities Test (SDMT) and the Montreal Cognitive Assessment (MoCA) in addition to the Brief Fatigue Inventory (BFI) and the Beck Depression Inventory-Fast Screen (BDI-FS).ResultsAt baseline, the SARS-CoV-2-positive group presented with higher levels of fatigue in the BFI. In both the SARS-CoV-2-positive and SARS-CoV-2-negative groups, some subjects presented attention and memory deficits, defined as a z-score < −1,65 on the SDMT or < 26 points on the MoCA (SDMT: 22.9% in the positive and 8.8% in the negative group, p = 0.024; MoCA: 35.6% in the positive and 27.3% in the negative group, p = 0.313). MoCA and SDMT improved over time in both groups. For MoCA scores, a significant difference between the two groups was only seen at the first follow-up. SDMT z-scores did not differ at any time between the groups.ConclusionThese results support previous evidence that mild SARS-CoV-2 infections are associated with increased fatigue. However, we found relevant rates of cognitive impairment not only in the infected but also in the control group. This underlines the importance of including a control group in such investigations.